Orange Juice Improve the Food Intake and Cholesterol Concentration in Patients with Chronic Hepatitis C - Goncalves, Danielle R. [UNESP]; Lima, Claudia G. [UNESP]; Ferreira, Paula S. [UNESP]; Costa, Paulo [UNESP]; Cesar, Thais B. [UNESP]; Fla State Hort Soc (Florida State Horticultural Soc, 2015)
Hepatitis C virus (HCV) causes liver inflammation and alterations in liver metabolism, resulting in nutritional and biochemical disorders. Supplementation with antioxidants, such as vitamins, minerals, and flavonoids, has been suggested to minimize the effects of chronic hepatitis C and contribute to liver protection. The present study assessed whether orange juice, which is rich in vitamin C, carotenoids, and citrus flavonoids, may contribute to the treatment of patients with chronic hepatitis. Anthropometric, dietary, and biochemical parameters, including C-reactive protein (CRP), were measured in 46 adult patients of both genders who were diagnosed with chronic hepatitis C. Following regular use of orange juice as a dietary supplement for eight weeks, no alterations were found in the patients' body weight or body fat, but waist circumference exhibited a significant reduction. The serum levels of total cholesterol, low-density lipoprotein (LDL), triglycerides, and CRP decreased in all of the patients. The intake of orange juice minimize some of the alterations caused by HCV, possibly due to its bioactive components, and might, therefore, serve as an adjuvant in the treatment of patients with chronic hepatitis C.
Keywords: liver inflammation; dietary intake; citrus flavanones; vitamin C